The neurology of HIV infection - Brew, Bruce (Handbook of clinical neurology, 2018)
"The Neurology of HIV Infection covers all aspects of nervous system involvement and pathology in HIV-infected individuals. Specialists in this field cover epidemiology, global aspects, pathology and pathogenesis of nervous system disease in HIV-infection. All complications, including the pathology caused by HIV itself and all opportunistic infections of the nervous system are reviewed in detail. Both central nervous and peripheral nervous system complications, including neuropathies and myopathies, are discussed. Key chapters on global developments, HIV-associated neurocognitive disorders, IRIS, stroke and neuro-aids in children complete this volume."--Publisher's description